Business and administrative communication - Locker, Kitty O.; Kienzler, Donna S. (New York McGraw-Hill/Irwin, 2013)
Focuses on the rhetorical emphases of audience, purpose, and context to allow communicators to shape their messages more appropriately to all channels and for all purposes. This title covers the topics in all forms of business communication.
pt. 1. The Building Blocks of Effective Messages -- pt. 2. The Communication Process -- pt. 3. Basic Business Messages -- pt. 4. The Job Hunt -- pt. 5. Proposals and Reports.
Includes bibliographical references and indexes.
Keywords: Business communication; Communication in management